2013
DOI: 10.1080/10803548.2013.11076968
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Among Slovenian Physical Education Teachers: A Cross-Sectional Study

Abstract: occupational health injuries physical educators age gender teaching level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
4
20
1
1
Order By: Relevance
“…Occupational risks have been reported to increase along with age (Kovač, Leskošek, Hadžić & Jurak, 2013a) at 7.6% per year. Likewise, increasing age generally increases the odds ratios for occupational health problems, however at a much lower rate than that for injuries.…”
Section: Pe Teachers' Work Abilitymentioning
confidence: 99%
“…Occupational risks have been reported to increase along with age (Kovač, Leskošek, Hadžić & Jurak, 2013a) at 7.6% per year. Likewise, increasing age generally increases the odds ratios for occupational health problems, however at a much lower rate than that for injuries.…”
Section: Pe Teachers' Work Abilitymentioning
confidence: 99%
“…This study adds to the knowledge about the acoustic teaching/learning conditions in sport halls. The research revealed that the acoustic conditions in Slovenian school sport halls are poor, which makes it more difficult for pedagogic processes to be conveyed and consequently causes problems for PE teachers who identify voice disorders as their second most important professional health problem (Kovač et al, 2013). Differences in acoustics exist between the individual groups of sport halls.…”
Section: Discussionmentioning
confidence: 99%
“…While students experience problems in hearing teachers due to the noisy environment and consequently, pay less attention in a large space, teachers experience problems in making themselves sufficiently loud in order to overcome the noise in the environment. Accordingly, problems with voice (Kovač, Leskošek, Hadžić, & Jurak, 2013;Simberg, Sala, Vehmas, & Laine, 2005; and hearing (Kovač et al, 2013;Lemoyne et al, 2007) are among the most common professional health problems in PE teachers. Due to the previously described acoustic working conditions, PE teachers are more prone to problems with their voice than other teachers (Jonsdottir, Boyle, Martin, & Sigurdardottir, 2002;Preciado, Perez, Calzada, & Preciado, 2005;Smith, Kirchneret al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As students, due to noise, can barely hear their teachers and therefore their attention is reduced during classes in a larger space, teachers barely manage to be loud enough to overcome the surrounding noise and convey the desired message to students. Therefore, voice (Kovač, Leskošek, Hadžić, & Jurak, 2013;Simberg, Sala, Vehmas, & Laine, 2005;Smith, Kirchner, Taylor, Hoffman, & Lemke, 1998) and hearing problems (Kovač et al, 2013;Lemoyne, Laurencelle, Lirette, & Trudeau, 2007) are among the most common occupational health problems faced by physical education teachers. Due to the above-described working conditions, physical education teachers have voice problems more often than other teachers do (Jonsdottir, Boyle, Martin, & Sigurdardottir, 2002;J.…”
Section: Noise In Sports Hallsmentioning
confidence: 99%